Investigation of p‐contact performance for indium rich InGaN based light emitting diodes and solar cells. Issue 4 (17th November 2016) - Alam, Saiful; Sundaram, Suresh; Haas, Helge; Li, Xin; El Gmili, Youssef; Jamroz, Miryam E.; Robin, Ivan C.; Voss, Paul L.; Salvestrini, Jean‐Paul; Ougazzaden, Abdallah
Abstract : We report on the optimization of p‐GaN layers for high indium (In) content InGaN applications by optimizing temperature, precursor CP2 Mg flow rate and III/V ratio and report also on the optimization of p‐contact performance. Using MOVPE, a 150 nm thick p‐type GaN with moderate Mg doping and a 50 nm contact layer with high Mg doping concentration were grown on standard GaN templates at growth temperatures in the range of 850–1000 °C. Hall measurement yields hole concentration of 4.8 × 10 17  cm −3 for the optimized sample. SIMS shows Mg concentration of 1.7 × 10 20  cm −3 on average in the heavily doped and 4 × 10 19  cm −3 on average in the moderately doped p‐GaN layer for the optimized p‐GaN. A multilayer Pd/Ag/Ni/Au metal contact has been deposited on this p‐GaN and studied using the CTLM technique. Optimization of both p‐GaN layers and p‐contact processing led to a low resistance contact with specific contact resistivity of 6 × 10 −4  Ω cm 2 . We believe, the very high Mg concentration of the surface layer in intimate contact with the contact metal reduces the Schottky barrier height and band bending. This optimization of p‐GaN is an important step towards high efficiency green LEDs and solar cells.